Evaluating the Efficacy of Elaborative Strategies for Remembering Expository Text - Boudreau, Rhonda L.; Wood, Eileen; Willoughby, Teena; Specht, Jacqueline (Alberta Journal of Educational Research, 1999)
This study investigated whether elaborative interrogation would be an effective learning strategy for lengthy expository text. One hundred undergraduates (65 females and 35 males) comprised the study's five experimental groups: (a) unsupported elaborative interrogation, (b) self-study, (c) repetition, (d) elaborative interrogation with preunderlined main ideas, and (e) elaborative interrogation with preunderlined main ideas plus structured why questions. All students read an eight-page passage on childhood education, studied the main ideas (preidentified or not), used their instructed strategies, and completed a free recall and multiple-choice test. Of interest is that in unsupported conditions students had difficulty recognizing the main ideas in the passage. Elaborative interrogation was maximized when supported with preunderlined ideas and also was enhanced by providing specific why questions in addition to preunderlined ideas.